Adrenomedullin orchestrates treatment resistance in hepatocellular carcinoma via immune microenvironment remodeling - Gao, Xixi; Sun, Yongliang; Huang, Jia; Xu, Li; Huang, Hanchun; Yang, Zhiying (Frontiers in Genetics, 2025)
BackgroundHepatocellular carcinoma (HCC) displays marked cellular heterogeneity and immune microenvironment complexity that fundamentally influence transcatheter arterial chemoembolization (TACE) treatment responses and patient outcomes. Deciphering the molecular architecture underlying therapy resistance remains essential for advancing precision oncology in HCC management.MethodsWe integrated four single-cell RNA sequencing cohorts with bulk transcriptomic datasets and longitudinal clinical annotations from The Cancer Genome Atlas Liver Hepatocellular Carcinoma database and Gene Expression Omnibus repositories to perform multidimensional analyses. Computational frameworks including single-cell Phenotype Associated Score (scPAS), high-dimensional weighted gene co-expression network analysis (hdWGCNA), and Single-Cell Regulatory Network Inference and Clustering (SCENIC) were deployed to identify resistance-linked cellular subpopulations and pivotal regulatory modules. Functional validation employed adrenomedullin (ADM)-depleted Huh7 cellular models and xenograft tumor-bearing mouse systems, with mechanistic interrogation via Western immunoblotting, quantitative reverse transcription polymerase chain reaction, and Kaplan-Meier survival estimation to confirm ADM biological functions and clinical relevance.ResultsWe identified a TACE-resistant malignant cell subset (scPAS+) characterized by pronounced activation of glycolytic, hypoxic, and epithelial-mesenchymal transition pathways alongside overexpression of resistance-conferring genes including LINC00221, hexokinase 2, and alpha-fetoprotein. This cellular phenotype demonstrated robust associations with TACE non-responsiveness, sorafenib cross-resistance, and abbreviated patient survival. Patient stratification based on scPAS + signature genes delineated two distinct molecular subgroups: the scPAS + -enriched cohort exhibited marked TACE refractoriness, elevated sorafenib failure rates, immunosuppressive microenvironmental architecture, and diminished 5-year survival probability. Mechanistic investigations established ADM as a critical driver orchestrating this resistance phenotype. ADM depletion attenuated Huh7 cell proliferative capacity, migratory potential, and invasive behavior, reduced xenograft tumor burden in murine models, and substantially potentiated sorafenib antitumor efficacy.ConclusionThis study delineates an ADM-driven TACE-resistant HCC cellular subtype (scPAS+) that functions simultaneously as a prognostic biomarker and actionable therapeutic target for circumventing treatment resistance.